Tourism and Hospitality Essentials (THE) Journal, Vol.II, No.1, 2012 - 291 PENGARUH PROGRAM GREEN MARKETING DI HOTEL SHANGRI-LA JAKARTA TERHADAP GREEN CONSUMER BEHAVIOR (Survei Pada Tamu yang Menginap di Hotel Shangri-la Jakarta) - Desliana, Anasti; Andari, Rini (Universitas Pendidikan Indonesia, 2012)
Tourism holds an important role as a major contribution for economy of a country not least for Indonesia. Tourism activity can not be separated from the various tourism sectors are mutually supportive and integrated with one another so as to attract tourists to visit Indonesia. Hospitality industry is an important industry in tourism activity due to the hospitality industry is one industry that high contribute to the tourism sector particularly in Jakarta. Jakarta as the capital city of Republic of Indonesia has the potential to attract tourists to the fulfillment of needs in terms of lodging accommodations in great demand by the management of international chain hotels to expand its market share by establishing a network of hotels in Jakarta. The importance of the marketing strategy undertaken by the hotel a top priority with progress and about eco-friendly lifestyle imposed by the Hotel Shangri-La Jakarta. So in general the strategy undertaken by the Hotel Shangri-La Jakarta is the green marketing. Therefore, the research done in the hope that green marketing is a strategy of influence in the creation of green consumer behavior. In this study, the independent variable (X) is green marketing which has three sub variable are green value-Addition process, green management systems, and green products. Variable (Y) is green consumer behavior. The study was conducted during six months from September 2011 until February 2012 by using systematic random sampling as technique sampling. The results showed that green marketing significantly influence green consumer behavior. Factors of green marketing that gives a large effect is green management systems in Hotel Shangri-La Jakarta and the lowest factors in green marketing is green products in Hotel Shangri-La Jakarta.